Effect of acupoint application of Cortex Magnoliae Officinalis powder on promoting the recovery of gastrointestinal function after abdominal surgery (厚朴粉足三里穴位贴敷促进腹部手术后胃肠功能恢复效果观察) - YANG Eenhui (杨恩慧); XIA Mei (夏美); LIU Guopei (刘国培); GUO Li (郭立) (Journal of International Translational Medicine Limited, 2024)
Objective To investigate the effect of acupoint application of Cortex Magnoliae Officinalis powder on promoting the recovery of gastrointestinal function after abdominal surgery. Methods Totally 60 patients undergoing abdominal surgery were randomly divided into the study group and control group, with 30 cases in each group. Patients in the control group received routine nursing after surgery, and those in the study were given acupoint application of Cortex Magnoliae Officinalis powder on Zusanli (ST36) in addition to routine nursing. The time to first passing gas and defecation after operation and the bowel sounds were compared between two groups. A self-made questionnaire was used evaluate patient's satisfaction with nursing service. Results The time to recovery of bowel sounds, first passing gas and defecation after operation in the study group were shorter than those in the control group(P＜0. 01). The overall satisfaction rate in the observation group was higher than that in the control group (P＜0. 01). Conclusion The acupoint application of Cortex Magnoliae Officinalis powder is effective to promote the recovery of gastrointestinal function and reduce the discomfort symptoms after abdominal surgery. (目的 探究中药厚朴粉足三里穴位贴敷促进腹部手术患者术后胃肠功能恢复的效果。方法 选取2022年7月-2023年7月医院收治的行腹部手术的60例患者为研究对象, 随机分为研究组和对照组, 各30例。对照组接受常规术后护理, 研究组在对照组基础上开展穴位贴敷治疗。对比两组患者肠鸣音恢复时间、首次排气和排便时间, 评价护理满意度。结果 研究组患者术后首次排气时间、排便时间、肠鸣音恢复时间均较对照组患者缩短, 差异有统计学意义(P＜0. 01)。研究组总满意率高于对照组, 差异有统计学意义(P＜0. 01)。结论 厚朴粉足三里穴位贴敷可有效促进腹部手术患者术后胃肠功能的恢复, 减少术后不适症状。)